1998
DOI: 10.2307/3870596
|View full text |Cite
|
Sign up to set email alerts
|

PEI1, an Embryo-Specific Zinc Finger Protein Gene Required for Heart-Stage Embryo Formation in Arabidopsis

Abstract: We used virtual subtraction, a new gene isolation strategy, to isolate several genes of interest that are expressed in Arabidopsis embryos. These genes have demonstrated biological properties or have the potential to be involved in important biological processes. One gene isolated by virtual subtraction is PEI. It encodes a protein containing a Cys3His zinc finger domain associated with a number of animal and fungal transcription factors. In situ hybridization results showed that PEI1 is expressed throughout t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
96
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(100 citation statements)
references
References 0 publications
1
96
0
3
Order By: Relevance
“…CDM1 encodes a protein with TZF domains, each containing three Cys and one His that coordinate a zinc atom (Lai et al, 2000); this type of zinc finger protein is involved in various developmental processes and environmental responses in plants (Li and Thomas, 1998;Sun et al, 2007;Kim et al, 2008;Wang et al, 2008;Lin et al, 2011). TZF proteins were initially identified in animals with two highly similar C-X8-C-X5-C-X3-H motifs (X represents variable amino acids) that are separated by 18 amino acids between the carboxyl terminal H of the first zinc finger and the amino terminal C of the second zinc finger (Blackshear et al, 2005).…”
Section: Cdm1 Might Be An Rna-binding Proteinmentioning
confidence: 99%
“…CDM1 encodes a protein with TZF domains, each containing three Cys and one His that coordinate a zinc atom (Lai et al, 2000); this type of zinc finger protein is involved in various developmental processes and environmental responses in plants (Li and Thomas, 1998;Sun et al, 2007;Kim et al, 2008;Wang et al, 2008;Lin et al, 2011). TZF proteins were initially identified in animals with two highly similar C-X8-C-X5-C-X3-H motifs (X represents variable amino acids) that are separated by 18 amino acids between the carboxyl terminal H of the first zinc finger and the amino terminal C of the second zinc finger (Blackshear et al, 2005).…”
Section: Cdm1 Might Be An Rna-binding Proteinmentioning
confidence: 99%
“…A67815). A full-length SERK1 cDNA was isolated from an Arabidopsis cDNA library made from flower buds and opened flowers (Li and Thomas, 1998). This cDNA consisted of an open reading frame of 1,875 nucleotides and 194 nucleotides of 5Ј-untranslated region (GenBank accession no.…”
Section: Molecular Cloning Of Atserk1mentioning
confidence: 99%
“…Phages (1.5 ϫ 10 6 ) from an amplified Lambda-ZAPII (Stratagene) cDNA library made from flower buds and open flowers (Li and Thomas, 1998) were plated according to the manufacturer's protocol. The plaques were hybridized with a 4-kb XbaI fragment of genomic AtSERK1 gene containing most of the coding sequence, and five positives were recovered and characterized by end sequencing.…”
Section: Library Screening Subcloning and Dna Sequencingmentioning
confidence: 99%
“…Most of the characterized CCCH-type zinc finger proteins are associated with RNA metabolism by binding to the target mRNA (Cheng et al, 2003;Delaney et al, 2006;Lai et al, 2006;Hurt et al, 2009), and only two, Arabidopsis PEI1 and rice OsLIC, are suggested to transcriptionally regulate gene expression by binding to DNA (Li and Thomas, 1998;Wang et al, 2008b). In addition, OsLIC harbors an EELR-type activation domain for regulating gene transcription in yeast (Wang et al, 2008b).…”
Section: C3h12 May Function As An Rna-binding Proteinmentioning
confidence: 99%
“…Arabidopsis PEI1, required for embryo development, can bind to DNA and functions as an embryo-specific transcription factor (Li and Thomas, 1998). Rice OsLIC (for Oryza sativa LEAF AND TILLER ANGLE INCREASED), containing only one CCCHtype zinc finger motif, can bind to both DNA and RNA and putatively controls plant architecture as a transcription activator (Wang et al, 2008b).…”
mentioning
confidence: 99%